Phonons in A3C60 Lattice and Structural Dynamics - Sven Larsson (Advances in Condensed Matter Physics)
The critical temperature (𝑇𝐶) of superconductivity in A3C60 compounds is generally lower smaller with alkali atoms (A). Furthermore 𝑇𝐶 decreases with applied pressure. In the BCS model, these trends are explained by the lower density of states at the Fermi level for a decreased lattice constant (R). There is more than one counterexample, however, suggesting that BCS does not give the whole truth. The most important one is that the compound with the largest lattice constant, Cs3C60, is not superconducting at all at ambient pressure. In this paper we derive a novel model where a negative lattice contribution to Hubbard U, proportional to 1/R, is taken into account. It is possible to explain why A3C60 compounds with A = Li, and Na have a low 𝑇𝐶 or are not superconducting at all, and why Cs3C60 is superconducting only at applied pressure and then with the highest 𝑇𝐶 of all C60 alkali fullerides. It is concluded that the density of states mechanism derived in the BCS model is in doubt. Nevertheless superconductivity in A3C60 depends on electron-phonon coupling. The dominating phonon is the bond stretching Ag phonon, a breathing phonon for the whole fullerene molecular ion.